2022
DOI: 10.1001/jamanetworkopen.2022.9581
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Private Equity Acquisition and Outcomes of Acute Medical Conditions Among Medicare Beneficiaries

Abstract: Key Points Question What is the association between private equity (PE) acquisition of short-term acute care hospitals and measures of comorbidity, mortality, readmission, length of stay, and spending among Medicare beneficiaries admitted to the hospital with 1 of 5 acute medical conditions? Findings In this cross-sectional study of more than 21 million Medicare beneficiaries with 5 different acute medical conditions who were hospitalized at short-term acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…6,7 Early research has found hospital acquisitions to be associated with a small increase in charge-to-cost ratio and net income, 10 a higher likelihood of providing more profitable hospital-based services, and mixed effects on quality. 9,12 It is unclear whether these findings generalize to physician practices, which have different business structures, service lines, and management practices.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Early research has found hospital acquisitions to be associated with a small increase in charge-to-cost ratio and net income, 10 a higher likelihood of providing more profitable hospital-based services, and mixed effects on quality. 9,12 It is unclear whether these findings generalize to physician practices, which have different business structures, service lines, and management practices.…”
Section: Introductionmentioning
confidence: 99%
“…22 Further, hospital acquisition reduced in-hospital and 30-day mortality in patients admitted with acute myocardial infarction. 21 On the negative side, residents of acquired nursing homes experienced a 10% increase in short term mortality and declines in well-being (eg, lower mobility, higher pain intensity scores). 5,6 In this context, survey data support physician concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, findings with respect to the effects of acquisition on patient quality are mixed. 5,21 On the positive side, a study demonstrated that acquired hospitals improved their performance on quality measures for patients hospitalized with acute myocardial infarction and pneumonia. 22 Further, hospital acquisition reduced in-hospital and 30-day mortality in patients admitted with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…rivate equity firms have increasingly acquired hospitals and physician practices. [1][2][3][4][5][6][7][8][9][10] This has garnered scrutiny from policymakers and the public, including the Biden administration and several US Senate and House committees. [11][12][13][14] Central to the concern over such acquisitions are the implications for patients-notably the quality of care-given the incentives of private equity to generate financial returns on investment quickly.…”
mentioning
confidence: 99%
“…Within private, nongovernment hospitals, private equity has an often distinct business model, in which the acquired entity typically assumes debt in the initial acquisition and is sold within a short time frame (often within 3-7 years). 6 Early evidence [7][8][9][10] showed that private equity acquisition was associated with increased charges, reduced staffing, use of profitable service lines, a decreased proportion of patients with Medicare, and increased net income.…”
mentioning
confidence: 99%